Accounting treatment for corporate zakat: a critical review - Adnan, Muhammad Akhyar; Abu Bakar, Nur Barizah (Emerald Group Publishing, 2009)
Purpose – The purpose of this paper is to review the accounting treatments for corporate zakat, as advocated by accounting standards and guidelines, as well as those been practised by relevant corporations. The aim is to determine their appropriateness and adherence to both the Islamic as well as the accounting theoretical perspectives.